Innovative methods of managing research testing of gas turbine installations for terrestrial applications - Шитикова, Елена Викторовна; Табунщик, Галина Владимировна; Разношинский, Виктор Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
The article deals with the questions of a efficient management by research test process of the gas turbine units for terrestrial usage. Authors have executed reengineering of research test process taking into account specificity of complex research tests of the gas pumping station.